Clinical Validation of Adjusted Corneal Power in Patients with Previous Myopic Lasik Surgery - Vicente J. Camps; David P. Piñero; Veronica Mateo; Celia García; Alberto Artola; Rafael Pérez-Cambrodi; Pedro Ruiz-Fortes (Journal of Ophthalmology)
Purpose. To validate clinically a new method for estimating the corneal power (Pc) using a variable keratometric index (nkadj) in eyes with previous laser refractive surgery. Setting. University of Alicante and Medimar International Hospital (Oftalmar), Alicante, (Spain). Design. Retrospective case series. Methods. This retrospective study comprised 62 eyes of 62 patients that had undergone myopic LASIK surgery. An algorithm for the calculation of nkadj was used for the estimation of the adjusted keratometric corneal power (Pkadj). This value was compared with the classical keratometric corneal power (Pk), the True Net Power (TNP), and the Gaussian corneal power (PcGauss). Likewise, Pkadj was compared with other previously described methods. Results. Differences between PcGauss and Pc values obtained with all methods evaluated were statistically significant (p<0.01). Differences between Pkadj and PcGauss were in the limit of clinical significance (p<0.01, loA [−0.33,0.60] D). Differences between Pkadj and TNP were not statistically and clinically significant (p=0.319, loA [−0.50,0.44] D). Differences between Pkadj and previously described methods were statistically significant (p<0.01), except with PcHaigisL (p=0.09, loA [−0.37,0.29] D). Conclusion. The use of the adjusted keratometric index (nkadj) is a valid method to estimate the central corneal power in corneas with previous myopic laser refractive surgery, providing results comparable to PcHaigisL.